Perspectives on international relations : power, institutions, and ideas - Nau, Henry R. , 1941- (SAGE, 2015)
Providing students with an even-handed presentation of realism, liberalism, constructivism and critical theory, this book expertly applies those perspectives in every chapter and trains students to think critically about the world's most pressing issues